Memory and Complicity : Migrations of Holocaust Remembrance (Book collections on Project MUSE., 2015)
This book explores and celebrates the outstanding Special Collections of The University of Manchester Library. These collections of rare books, manuscripts, archives, maps and visual materials are extraordinarily rich and diverse. They span 5,000 years and six continents, and include almost every format ever used for written communication. Many derive from the superlative collections purchased by Enriqueta Rylands for the magnificent library she founded as a memorial to her husband John. The book features over 150 key items from across the collections. Thirteen thematic chapters contain short essays on individual items by over sixty contributors--curators and experts in particular fields. Every item is beautifully illustrated in full colour and an extended introduction charts the history and context of the collections. This book will appeal to a broad readership--lovers of books and libraries, and anyone interested in literature, art, history, the history of ideas and collecting.